Energetic ion injection and formation of the storm-time symmetric ring current - L. Xie; Z. Y. Pu; X. Z. Zhou; S. Y. Fu; Q.-G. Zong; M. H. Hong (Annales Geophysicae, 2006)
An extensive study of ring current injection and intensification of the storm-time ring current is conducted with three-dimensional (3-D) test particle trajectory calculations (TPTCs). The TPTCs reveal more accurately the process of ring current injection, with the main results being the following: (1) an intense convection electric field can effectively energize and inject plasma sheet particles into the ring current region within 1–3 h. (2) Injected ions often follow chaotic trajectories in non-adiabatic regions, which may have implications in storm and ring current physics. (3) The shielding electric field, which arises as a consequence of enhanced convection and co-exists with the injection and convection electric field, may cause the original open trajectories of injected ions with higher energy to change into closed ones, thus playing a role in the formation of the symmetric ring current.